Financial development and economic growth : evidence from panel data - Yugindri, Baskaran (2018)
This study explores the importance of financial development towards economic growth. This study examines the relationship between financial development and economic growth in OECD countries. Real GDP per capita is used to measure economic growth. To measure financial development three different variable is chosen namely liquid liabilities (M2), credit to private sector and Financial Technology (Fintech). Besides that, there are also few other variables that had been used a control variable which is Energy Consumption, Capital Formation and Net Trade. Panel Ordinary Least Square and Granger Causality had been employed to determine the relationship between the financial development and economic growth. Based on the result, we can conclude that financial development significantly impacts the economic growth of a country. However, from the empirical result the credit provided to private sector and Fintech have negatively impacted the economic growth. Despite, liquid liabilities has a positive relationship between economic growth. Besides that, from the result the capital formation and net trade had a positive relationship toward economic growth. Furthermore, the energy consumption has a negative impact on economic growth. From the empirical result we can conclude that there is a bidirectional causality flow between credit to private sector and GDP. besides that, GDP has a Uni-directional relationship flow from GDP to Liquid liabilities and Fintech. In general, a well-developed financial system is an essential element in boosting economy.